In vitro amplification of H-type atypical bovine spongiform encephalopathy by protein misfolding cyclic amplification - O'Connor, M.J.; Bishop, Keith; Workman, Robert G.; Maddison, Ben C.; Gough, Kevin C. (Taylor & Francis, 2017)
The in vitro amplification of prions by serial protein misfolding cyclic amplification has been shown to detect PrPSc to levels at least as sensitive as rodent bioassay but in a fraction of the time. Bovine spongiform encephalopathy is a zoonotic prion disease in cattle and has been shown to occur in three distinct forms, classical BSE (C-BSE) and two atypical BSE forms (L-BSE and H-BSE). Atypical forms are usually detectedin asymptomatic, older cattle and are suggested to be spontaneous forms of the disease. Here, we show the development of a serial protein misfolding cyclic amplification method for the detection of H-BSE. The assay could detect PrPSc from 3 distinct experimental isolates of H-BSE, could detect PrPSc in as little as 1 x 10-12 g of brain material and was highly specific. Additionally, the product of serial protein misfolding cyclic amplification at all dilutions of seed analysed could be readily distinguished from L-BSE, which did not amplify, and C-BSE, which had PrPSc with distinct protease K-resistance and protease K-resistant PrPSc molecular weights.